REVITALIZATION OF SURABAYA'S OLD PRECINCT: CHALLENGE AND STRATEGY OF GROWTH - Wijaya, Verina; Indrianto, Agoes Tinus Lis; Oktavio, Adrie (Universitas Multimedia Nusantara, 2025)
Abstract- The revitalization of Surabaya’s old precinct holds strong potential to enhance the city's tourism appeal and stimulate local economic development. This heritage-rich area has historical and cultural value, making it a strategic destination for both domestic and international tourists. However, several challenges hinder its development, including a lack of interactive attractions, insufficient public facilities such as cafés, rest areas, and toilets, as well as limited visitor engagement and short tourist stays. This study employs a qualitative descriptive research design, using triangulated data from in-depth interviews with government officials, heritage community members, and tourism practitioners, along with field observations and document analysis. The research aims to identify key strategies, opportunities, and constraints in revitalizing the precinct. Findings highlight the critical role of multi-stakeholder collaboration in revitalization efforts, where the synergy between the government, local communities, and the private sector is essential to success. The study also shows that improved infrastructure, enhanced public awareness, and creative tourism programming are necessary to sustain heritage tourism in the area. This study contributes to the discourse on sustainable urban heritage management and offers practical recommendations to policymakers seeking to balance conservation with tourism-driven economic growth in historic urban districts. Keywords: Heritage Tourism; Revitalization; Old Precinct; Economic Growth; Surabaya